Caribbean Report 04-01-1991 - Goffe, Leslie (anchor); Grant, Bernie (interviewee); Bennendijk, Chandra van (correspondent); Khan, Sharief (correspondent); Baptiste, Sandra (correspondent) (The British Broadcasting Corporation, 1991)
In this segment, Guyanese born, British Labour Party MP, Mr. Bernie Grant speaks about his recent visit to Iraq and explains the serious implications that the Caribbean regions face should a war occur in the Gulf. A report from Suriname explains the ‘coup by telephone’ which was conducted by the military and how one of the biggest floods in 50 years is seen in Suriname as a washing towards a fresh start. The impact of the Suriname coup on a neighbouring country,Guyana, is also featured. Finally, a report is given on the implementation date of CARICOM’s Common External Tariff and the appointment of a CARICOM Commissioner.
1. Headlines (00:00-00:34)
2. Mr. Bernie Grant speaks about his visit to Iraq and shares his views on Saddam Hussain and the political landscape of Iraq given the impending war in Baghdad (00:35-05:03)
3. . Paramaribo reporter, Chandra van Binnendijk explains why the military coup in Suriname was referred to as a ‘coup by phone’ . She also explains that the recent floods in Suriname is seen as a washing out of all the negativities that have taken place in the country and the dawn of a new beginning for the country (05:04-08:29)
4. Sharif Khan, correspondent from Guyana reports on how the Suriname coup can affect the neigbouring country of Guyana. (08:30-11:39)
Keywords: Grant, Bernie ǂq (Bernard Alexander Montgomery), ǂd 1944-2000; Caribbean Community.; Suriname -- Politics and Government.; Hussein, Saddam, ǂd 1937-2006; Iraq -- Politics and Government.; Guyana -- Politics and Government.; CARICOM.; Common External Tariff.; Coup by telephone -- Suriname.; London Afro-Asia Solidarity Movement.